Development of Virtual Try-On Application with Web Augmented Reality (AR) for Advertising - Raja Ahmad Shukri, Raja Nur Shafiqah (IRC, 2019)
Technology advancement brings about relentless and fast-paced change in today’s digital economy. Shoppers engage with and consume many types of content from various platforms simultaneously, hence posing challenges for businesses to retain customer loyalty and keep them hooked. For this reason, it is crucial for businesses to constantly adopt new and creative advertising methods to keep themselves connected and be in understanding with their audiences. This research found that there is a low engagement rate with users in current advertising practices and there are little solutions using augmented reality (AR) technology as a medium of advertising present in the Malaysian market. Therefore, this research project aims to analyze the requirements of virtual tryon web-based application with AR as an advertising tool for Malaysia-based fashion retailers, analyze and design the AR application and integrate the system in touchscreen panel. The requirements are gathered through survey from 33 participants. The system is developed under prototyping methodology and its scope for fashion wear is eyewear as well as hats and caps for Malaysian consumers. A total of 15 participants took part in the testing of the system and answered a survey under Technology Acceptance Model (TAM). This AR application in touchscreen panel can enrich the engagement of businesses and its target audiences and lead to increase in business revenue.